Problematika rabe jezika v upravno-sodni praksi - Kovač, Polonca (Teorija in praksa, 2017)
The use of language in law is a key component of the basic principles of democratic authority, particularly in administrative procedures where collisions between the public interest and the rights of individuals are solved. Hence, it is an issue dealt with by the language policies of both Slovenia and the EU. In order to examine how the prescribed principles and rights are implemented and to develop, based thereon, recommendations for future language policy, empirical research was conducted concerning the regulation and practice involving language rights in administrative matters before the Slovenian courts and the European Court of Justice in 2012-2016. The results for Slovenia show a high level of protection of Slovenian and the official languages of the protected minorities as well as of persons with disabilities. In matters involving foreign nationals and asylum seekers, where questions concerning the use of language are ever more frequent, the right to be heard in a foreign language is assessed case by case. The regulation and conduct of administrative procedures, with the use of language considered as a category of principle, thus appear to be relatively adequate. Systemic improvements are eventually recommended to achieve a more targeted regulation, greater clarity of provisions, and greater flexibility in regulating globalised administrative relations.
Keywords: Administrative procedure; Jezikovna politika; Language policy; Practice of law; Protection of rights; Sodna praksa; Upravni postopek; Zaščita pravic